Assessing Indonesia’s Investment Capital-Friendly Strategies: An Analysis of West Java’s Digital Licensing and Incentive Frameworks in 2025 - Christabel Saputra; Muhammad Glenn Akbar; Valerie Abigail Rusli; Vitto Valentino Prince (Syntax Literate, 2026)
This study examines the effectiveness of West Java’s integrated digital licensing and investment incentive frameworks in supporting investment growth and strengthening regional economic competitiveness in 2025. The research is motivated by Indonesia’s ongoing regulatory reforms through the Online Single Submission Risk-Based Approach (OSS-RBA), which aims to simplify business licensing procedures, improve legal certainty, and enhance investment governance through digitalization. The study aims to analyze the contribution of the OSS-RBA and One-Stop Integrated Service (PTSP) systems to investment realization and to evaluate the coherence between provincial regulations and the national investment framework. This research employed a mixed-method approach combining normative legal analysis and quantitative descriptive analysis. Primary data consisted of regional regulations, BKPM policies, and official investment reports, while secondary data were obtained from academic literature, institutional publications, and statistical records. Data collection was conducted through documentary studies and literature reviews, and the findings were analyzed using qualitative content analysis and descriptive statistical methods. The results indicate that the implementation of OSS-RBA and PTSP significantly improved licensing efficiency, procedural transparency, and investor accessibility, contributing to a 36.34% increase in total investment realization in West Java in 2025. Furthermore, the provincial regulatory framework demonstrated substantial alignment with national investment policies. In conclusion, digital licensing reforms supported by regulatory harmonization can effectively enhance investment performance and strengthen regional economic governance in Indonesia.